Constructing Low‐Solvation Electrolytes for Next‐Generation Lithium‐Ion Batteries. Issue 10 (31st August 2022) - Liu, Jipeng; Yuan, Botao; Dong, Liwei; Zhong, Shijie; Ji, Yuanpeng; Liu, Yuanpeng; Han, Jiecai; Yang, Chunhui; He, Weidong
Abstract: The realization of high‐concentration electrolytes (HCEs) is a benchmark breakthrough attributed to the modification of cation aggregation, which owns technical advantages over the widely used conventional electrolytes. Due to the high cost brought by the large amount of lithium (Li) salts, high viscosity, low Li + conductivity, and wettability of the HCE system, the concept of localized HCEs (LHCEs) is proposed to improve the aforementioned shortcomings without affecting the performances of high‐energy‐density batteries. Nevertheless, the effect factors of the weakly solvated structure of LHCEs have not been summarized, so it is urgent to conclude this direction to further survey the low‐solvation structure and properties. Hence, for the first time we offer a comprehensive and distinct overview on the electrolyte development, strategies for constructing low‐solvation structure, and scientific perspectives for lithium‐ion batteries, especially by focusing on the binding energies between cation and solvents, solvation and de‐solvation process, structure of novel solvents, and selection of Li salts. Emphasis is placed on the relevance of constructing low‐solvation structure and forming electrode/electrolyte interphases, and new insights into weakly solvated electrolytes associated with efficient solid electrolyte interphase and cathode electrolyte interphase layers are presented for developing next‐generation lithium‐ion batteries. Abstract : With low‐concentration electrolyte : This review offers a comprehensive and distinct overview on the electrolyte development, strategies for constructing low‐solvation structure, and scientific perspectives for lithium‐ion batteries, especially by focusing on the binding energies between cation and solvents, solvation and de‐solvation process, structure of novel solvents, and selection of Li salts.